Reliability of stability control in view of production process - Логанина, Валентина Ивановна; Круглова, Альбина Николаевна; Давыдова, Ольга Александровна (Technology audit and production reserves, 2013)
The data on the effect of measurement error on the probability of decision making on the products acceptance under statistical instability of the production process are given. It is shown that the objectivity of quality control depends on the accuracy of measuring devices, as well as the reproducibility of production process, characterized by the reproducibility indexes. This causes erroneous rejection of some effective items, the actual values of the controlled parameter of which lie in the tolerance zone. By the example of production of ceramic brick three variants were shown, which are characterized by different values of reproducibility indexes. The probability of errors of the first and second kind was calculated, which indicate the probability of the situation when the controlled item is effective, but it will be erroneously considered to be defective, and when the controlled item is defective, but it can be wrongly considered to be effective. It is established that the probability of the error of the first and second kind increases as the production process reproducibility reduces.